Penerapan Pembelajaran Kontekstual Untuk Meningkatkan Aktivitas Dan Hasil Belajar Matematika Siswa Kelas III Semester II SD Negeri 4 Pertima - Ni Luh Sumerini (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to (1) find out the increase in Mathematics learning outcomes in class II semester II of SD Negeri 4 Pertima in the 2016/2017 school year after the application of contextual learning and (2) to know the increase in learning activities in class II semester II of Pertima 4 2016/2017 lessons after the application of contextual learning. The results showed that the application of contextual learning can improve learning activities and learning outcomes of Mathematics in third grade students in the second semester of the academic year 2016/2017 in SD Negeri 4 Pertima. The average value of learning activities in the first cycle was 7.23 and the percentage of learning activities in the first cycle was 51.64% included in the less category. The average value of learning activities in the second cycle is 10.58 and the percentage of learning activities in the second cycle is 75.57%, included in the Good category. The average value of learning outcomes in the first cycle was 62.63 and the percentage of learning outcomes in the first cycle of 62.63% belonged to the sufficient category. The average value of learning outcomes in the second cycle is 87.25 and the percentage of learning outcomes in the second cycle is 87.25% included in the excellent category. Learning completeness in the first cycle of 75% experienced an increase in the second cycle to 100%. Based on the results of these studies it can be concluded that contextual learning can improve the activities and mathematics learning outcomes of students in grade III semester II SD Negeri 4 Pertima